An emotion recognition system: bridging the gap between humans-machines interaction - Ahmed Nouman; Hashim Iqbal; Muhammad Khurram Saleem (Institute of Advanced Engineering and Science, 2023)
Human emotion recognition has emerged as a vital research area in recent years due to its widespread applications in psychology, healthcare, education, entertainment, and human-robot interaction. This research article comprehensively analyzes a machine learning-based six-emotion classification algorithm, focusing on its development, evaluation, and potential applications. The study aims to assess the algorithm's performance, identify its limitations, and discuss the importance of selecting appropriate image descriptors for accurate emotion classification. The algorithm achieved an overall accuracy of 92.23%, showcasing its potential in various fields. However, the classification of specific emotions, particularly